Seroprevalence Study on West Nile Virus (WNV) Infection, a Hidden Viral Disease in Fars Province, Southern Iran - Masoumeh Amin; Morteza Zaim; Hamideh Edalat; Hamid Reza Basseri; Mohammad Reza Yaghoobi-Ershadi; Farhad Rezaei; Kourosh Azizi; Mostafa Salehi-Vaziri; Mohsen Ghane; Saideh Yousefi-Sharikabad; Sorna Dabaghmanesh; Sedigheh Kheirandish; et al. (Tehran University of Medical Sciences, 2020)
Background: West Nile Virus, a mosquito-borne flavivirus, causes a variety of symptoms in human, from asymptomatic infection to neuroinvasive disease. Several studies have been conducted on the seroprevalence of WNV infection in different areas from Iran. This study was performed to find the presence of antiviral antibodies in human serum among some high risk population and awareness of health care staff about symptom of the WNV infection. Methods: Study performed in ﬁve geographical districts based on high population of immigrant and domestic birds and prevalence of the antiviral antibodies in horses which was reported previously. Totally 150 human blood samples were collected during 2018. The samples collected from patients referred to the clinics. The ELISA method used to detect IgG and IgM antibody against WNV. Logistic regression models used to analyze the effect of sex, age, keeping birds and urban/rural residence on the risk of infection. The awareness of health care staff about symptom of infection surveyed. Results: From all blood donors, 41 samples (27.33%) showed positive to IgG antibody. From which 56.10% were males and remaining females. None of the mentioned factors had a significant relationship. Health care staff had less attention to the infection.  Conclusions: Although the prevalence of antibodies was relatively high, due to the similarity to other viral diseases, health care staff had less attention to the disease. The study showed that people in these areas have been exposed to the virus. Further research activities are recommended for control of this arbovirus.